Exploring Narratives of Adolescent-to-Parent Abuse - Oviedo, Sofia (2019)
Adolescent-to-parent abuse (APA) is an often hidden form of family abuse that evidences a breakdown in the parent-child relationship with damaging effects on the physical and emotional well-being of parents and youth. This study aimed to examine the experiences of parents affected by APA, the effects on the parent-child relationship, and on parent identity. It also explored how APA influenced the relationship dynamics during conflicts, how parents managed these conflicts, and how parents viewed their power within these interactions. Semi-structured interviews were conducted with 18 parents who resided in two major cities in the US (Seattle, WA and New York City). A phenomenological framework and thematic analysis were used to identify and develop three major themes: living in uncharted territory, “stuck in a cycle:” impacts of APA on family dynamics, and seeking help. Findings showed that parents experienced significant emotional and physical abuse, further compounded by the negative effects on the parent-child relationship, parenting, and parent identity. Parents also reported additional harmful effects on their other children. Mothers were found to be primarily affected by APA, which notably influenced their views on power in the parent-child relationship. Parents’ recommendations for increasing awareness of APA among families and practitioners are also provided. Findings are analyzed within a family systems and family power relations theoretical framework and implications for social welfare, policy, practice and future research are discussed